A Response to Pathways to Sustainability. (23rd October 2014) - Huckle, John
<x content-type="archive" xml:space="preserve">Abstract</x> There has been very limited progress along the pathways to sustainability sketched in my 1991 article. Some would argue we have taken several steps backwards. Environmental education is now more prepared to acknowledge the role of neoliberal global capitalism in promoting unsustainable development, and to associate sustainability with social movements and parties of the green left who urge new forms of economy and global democracy. Corporations and governments have been successful in linking education for sustainable development to ecological modernisation or light green versions of the status-quo, but in England, even the limited advance of a policy on sustainable schools under New Labour has been swept away by the present coalition government.